2003
DOI: 10.1590/s1519-566x2003000200026
|View full text |Cite
|
Sign up to set email alerts
|

Association of Ceracis cornifer (Mellié) (Coleoptera: Ciidae) with the bracket fungus Pycnoporus sanguineus (Basidiomycetes: Polyporaceae)

Abstract: Associação de Ceracis cornifer (Mellié) (Coleoptera: Ciidae) com o Fungo Pycnoporus sanguineus (Basidiomycetes: Polyporaceae) RESUMO-Duas novas coletas de Ceracis cornifer (Mellié) na Região Sudeste do Brasil são relatadas, descrevendo a associação dessa espécie com o fungo orelha-de-pau Pycnoporus sanguineus. A associação de outras espécies do grupo Ceracis furcifer Mellié com esse fungo é discutida. PALAVRAS-CHAVE: Ciinae, micetobionte, basidiocarpo ABSTRACT-Two new records of Ceracis cornifer (Mellié) in th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
13
0

Year Published

2007
2007
2021
2021

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 0 publications
0
13
0
Order By: Relevance
“…host fungi. However, species of the C. furcifer group are most frequently found in basidiomes of Pycnoporus sanguineus (L.) Murrill, 1904(LAWRENCE 1973, GUMIER-COSTA et al 2003, GRAF-PETERS et al 2011), a very common fungi occurring in open areas of tropical Brazil, seldom observed inside forests (C. Lopes-Andrade, pers. obs.).…”
Section: Discussionmentioning
confidence: 99%
“…host fungi. However, species of the C. furcifer group are most frequently found in basidiomes of Pycnoporus sanguineus (L.) Murrill, 1904(LAWRENCE 1973, GUMIER-COSTA et al 2003, GRAF-PETERS et al 2011), a very common fungi occurring in open areas of tropical Brazil, seldom observed inside forests (C. Lopes-Andrade, pers. obs.).…”
Section: Discussionmentioning
confidence: 99%
“…Original descriptions of species of the furcifer group provide scant occurrence data, that are sometimes inaccurate and there are few subsequent works citing information on these species. Mellié [ 1 ] cited the type-locality of C. cornifer solely as “Brésil” (=Brazil) and there are only a few other published records of the species from southeastern Brazil [ 9 ]. Ceracis simplicicornis was described from Buenos Aires (Argentina) and recorded from São Francisco de Paula (RS-Brazil) [ 10 ].…”
Section: Introductionmentioning
confidence: 99%
“…Here, the southern tip of Florida will be treated as part of the Neotropical region, and the surrounding areas as transitions to the Nearctic region. Therefore, all members of the furcifer group are essentially Neotropical [ 3 , 9 , 10 ], with a few records from the Nearctic region [ 3 ], and its species have allopatric distributions based on previously known material [ 3 ].…”
Section: Introductionmentioning
confidence: 99%
“…These members are considered mycetobiont because they depend upon the basidiocarps for food and breeding throughout their life span (Scheerpeltz and Höfler, 1948;Gumier-Costa et al, 2003;Jung, 2010). For example, Cis boleti preferentially colonizes in the fruiting bodies of fungi from the genus Trametes that are known as important wood decomposers.…”
mentioning
confidence: 99%